Sistem Informasi Manajemen Stok Toko Kelontong Berbasis Web untuk Pencatatan Stok di Toko Dandung - Bisma Muhammad Hermawan; Muhammad Abdulrahman Hakim; Rijal Arifin; Edy Susena (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This study is to develop a web-based inventory management information system for grocery merchants in order to speed up the stock recording process. The system is built according to the waterfall style of system development, using PHP and MySQL. Data collection techniques include observation, interviews, and literature research. As a result, store managers can improve operating efficiency and reduce errors in manual stocktaking by using a system that allows real-time product stock input, updating, and monitoring. This study provides a practical digital solution to support the digitization of small businesses in Indonesia.